Implementation of the Tadarus Keliling (Tarling) Program in Madrasah Ibtidayah as an Effort to Instill Self-Confidence in Students - Aprilliani, Linda Kurnia; Kaltsum, Honnest Ummi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: In the implementation of education, of course, it does not only prioritize learning but also the cultivation of national character. However, there are still those who view that learning science is more important than teaching character cultivation in children. The objectives of this study are: a) Describe the implementation of tarling activities at MIM PK Wirogunan; b) Knowing the impact of the mobile tadarus activity program on students' self-confidence character. Methodology: This type of research is qualitative phenomenology. This research was conducted at MIM PK Wirogunan Kartasura. The research subjects were the Principal, teacher representatives and students who participated in tarling activities. Data collection techniques include interviews, observation and documentation. Test the validity of the data in the form of triangulation of techniques and sources. Data analysis uses interactive techniques by collecting and analyzing data to develop a theory. With data analysis steps that include data collection, data reduction, data presentation, verification and conclusion drawing. Results: The results showed that a) The implementation of tarling at MIM PK Wirogunan Kartasura is carried out once a month on Friday of the first week for low classes, namely 1,2,3 and for high classes 4,5,6 in the second week. The purpose of this tarling activity program is to connect silahturahmi between student guardians and so that students get to know each other. The stages of this tarling program are: opening activities, core activities, other activities and closing activities. b) The implementation of the tarling activity program at MIM PK Wirogunan Kartasura can instill confident characters in students. The teacher's efforts in instilling confident character at MIM PK Wirogunan Kartasura through the tarling activity program are: giving responsibility, guiding, strengthening and motivating, providing apperception, and inviting students to communicate. Applications/Originality/Value: This research reveals that in a school it is very important to instill national character, especially self-confidence, to make it easier for students to adjust to their social environment.